Hubungan Metode Bermain, Cerita, dan Menyanyi (BCM) dengan Prestasi Belajar Siswa SD menurut Persepsi Mahasiswa UIN Maulana Malik Ibrahim Malang - Purniadi Putra (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
The use of play methods, stories and singing (BCM) is expected to be easily understood and can increase the child's motivation for the child to get a good achievement. In line with this statement that one way to move the child's achievement is to create a fun learning condition because if the child is happy with the lesson they are going through then their children get a good achievement. This research method using quantitative research. Research location in UIN Maulana Malik Ibrahim Malang. The results describe the amount of variance that can be explained by the fakor formed in each variable. The value of communalities for the play method is 0.979 means that 98% of the factors formed are able to explain the variance of the facility attributes that support the singing method. Communalities for the story method variable is 0.719 meaning that 79% of the factors formed are able to explain the variance of the facility attributes that support the story method, and for the singing method variable is 0.60 means that 60% of the factor is able to explain the variance of the attribute that supports the singing method.